Taxonomic review on the Trioserica Moser, 1922 species of China (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk; Liu, Wangang; Fabrizi, Silvia; Bai, Ming (Zootaxa, 2021)
In the present study the taxonomy of the species of the genus Trioserica Moser, 1922 from China is revised. We recorded so far six valid species, of which five resulted to be new to science: Trioserica cangyuanensis Ahrens, Liu & Fabrizi, new species, T. daweishana Ahrens, Liu & Fabrizi, new species, T. dinghushanica Ahrens, Liu & Fabrizi, new species, T. lilongensis Ahrens, Liu & Fabrizi, new species, and T. shiyiduiensis Ahrens, Liu & Fabrizi, new species. The habitus and male genitalia of the species are illustrated and maps of their known distribution are shown.